Developing a model that prescribes a feasible WFH Strategy to organizations: a study of the ICT sector in South Africa - Tripod, Ryan (Department of Information Systems, 2025)
This paper has performed a pragmatic analysis of work-from-home (WFH) strategies in order to prescribe Information Communication Technology (ICT) organisations in South Africa with a model to assess WFH Strategy feasibility. This resulted in the creation of the WFH-Strategy, Feasibility, and Capacity assessment model (WFH-SFCAM). A model that identifies the relationship between a WFH Strategy, the WFH Capacity, and the WFH Domain. It was found that, for a WFH Strategy to be feasible, a holistic review of the WFH Domain should be conducted by the Organisation. Meaning that the Organisational, Personal preferences, Job Description, Technological requirements, and External contexts must all be reviewed for a WFH Strategy to be designed feasibly. Furthermore, it was noted that the organisation is the owning domain of the WFH Strategy and benefits through increased performance, increased access and retention of talent, and decreased office space costs. Whilst employees experienced an improved quality of life, increased cost and time savings, and less risk to illness. However, employees did become less active. With additional changes to management of employees in the areas of performance and communication. Thus, this study found that WFH strategies are feasible in South African ICT organisations when managed and implemented appropriately.